Factor associated with central obesity among patients with non-communicable disease in Urban area of Gorontalo - Fitri Yani Arbie; Nuryani Nuryani; Fatmayanti Nawai; Ayu Bulan Febry KD; Vera Tasintimbang Harikedua; Nonce Nova Legi (AcTion: Aceh Nutrition Journal, 2025)
Non-communicable disease (NCD) is a chronic health condition caused by various factors, such as age, physical activity, obesity, and economic status, which can increase the risk of unhealthy living conditions. This study aimed to identify factors associated with the occurrence of central obesity in patients with NCDs using a quantitative approach with a cross-sectional study design calculated using the Slovin formula, involving 207 people who filled out the questionnaire instrument. Sample collection using stratified sampling with inclusion criteria for patients with NCD at five community health centers in Gorontalo City from June to October 2024. After normality testing, the independent sample t-test and Mann-Whitney U test were used to analyze the data. The research results showed the characteristics of the respondents with diabetes mellitus (52,7%) and hypertension (25,2%). The overall incidence of central obesity was 75,8%. Bivariate analysis indicated a relationship between physical activity (p=0,008), sex (p=0,000), smoking habits (p=0,000), long illness of NCDs (p=0,049), and the incidence of central obesity, while there was no association between family history of NCDs (p=0,935), income (p=0,941), and central obesity. The factors related to the incidence of central obesity in NCDs patients are physical activity, sex, smoking habits, and prolonged illness.